Exploring the Role of β-Sitosterol, Genistein, and Emodin in Periodontal Regeneration - Prabhu M. Natarajan; Mohamed A. Jaber; Vidhyarekha Umapathy; Bhuminathan Swamikannu; Manickam S Nandhini; Vijay B. Desai; Mohammad K. S. Khot (Journal of Pharmacy and Bioallied Sciences)
The incidence rate of periodontal diseases is high, which affects the quality of life of patients, and is one of the main causes of adult dentition defects. Periodontal diseases cause the periodontal intraosseous defect. If not treated in time, it can lead to alveolar bone resorption and defect, periodontal attachment loss, teeth loosening, and complete tooth loss. Bone grafting is to repair periodontal defects by transplanting materials to restore the anatomical morphology of the alveolar bone and the function of periodontal tissue. This study evaluated the osteogenic activity of 3 phytochemicals - β-sitosterol, Genistein, and Emodin when compared to hydroxyapatite alone and tested the in vitro osteogenic activity of the prepared graft materials. The procedure for adhesion, viability, proliferation, and alkaline phosphatase activity was reported. The addition of phytochemicals to hydroxyapatite enhances its bioactivity. This is based on adhesion, viability, proliferation, and ALP activity assessed on the seventh and ninth days respectively in the prepared samples of the phytochemical. Based on the successful results of this study an efficient and cost-effective osteogenic bone graft with effective clinical application can be proposed. The phytochemicals β-Sitosterol, Genistein, and Emodin can be mixed in the optimum quantities to the hydroxyapatite grafts to be used as periodontal regenerative materials. In addition, such optimized concentrations can be further studied for their application to other alloplastic resorbable materials to be used for the grafting of larger defects.